An Axiomatic Foundation of the Ecological Footprint - Thomas Kuhn; Radomir Pestow; Anja Zenker (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2018)
The objective of this paper is to provide an axiomatic foundation to the ecological footprint developed and refined by the authors in the Global Footprint Network, among others. For this purpose, five axioms are proposed which represent general properties any ecological footprint measure should fulfill. We show that an index exists which is unique up to a coefficient to be chosen arbitrarily. As an implication, footprints have to be measured on a ratio scale. This result supports the conventional unit of measurement (land area) which itself is represented by a ratio scale. In this respect, our index differs from the compound-based ecological footprint index in which the norm is missing and, therefore, it is implicitly set equal to one. Apart from that we find, as the most important result, that the ad-hoc design of the commonly applied ecological footprint index has been given an axiomatic foundation.
Keywords: Q13; Q41; Q43; C43; 330; Ecological Footprint Index; Axiomatic Foundation; Measurement Theory; Overshoot Day; Sustainable Welfare